DETERMINANTS OF INTEREST IN USING E-MONEY AMONG STUDENTS - Triesti Candrawati (KRISNA: Kumpulan Riset Akuntansi, 2025)
Current technological advances have had a huge impact on the development of payment instruments. E-money is a form of payment that is growing rapidly at this time. The use of e-money has several differences compared to paper money, primarily in terms of practicality and security aspects. A very big impact is felt on human life with advances in technology and information. The purpose of this research is to determine what determinants can influence students to use e-money in making payment transactions. The population of 188 students in the Management Accounting Study Program of Malang State Polytechnic Population. Meanwhile, 84 students were selected using a purposive sampling method. The method of analysis in this study employs multiple regression analysis to identify factors that influence students' use of e-money. The results of this study conclude that the use of e-money is positively and significantly influenced by the variable Perceived usefulness and Perceived ease of use, but the variable perceived cost does not have a positive and significant effect on the interest in using e-money